PENGARUH BODY MASSAGE TERHADAP TINGKAT DEPRESI RINGAN IBU NIFAS DI PMB FATMAWATI KOTA JAMBI - Imelda Imelda; Miptahul Jannah; Diniati Diniati; Suryani Suryani (NHM PRESS, 2022)
The incidence of postpartum depression according to the WHO report is estimated that women who give birth and experience mild depression range from 10 per 1000 live births and moderate or severe postpartum depression ranging from 30 to 200 per 1000 live births. This study was a quasi-experimental study with the design of one group pretest-posttest to determine the effect of body massage on the level of mild depression in postpartum mothers at PMB Fatmawati, Jambi City. Time of study in January − July 2019. The population of this study was all postpartum mothers who gave birth at PMB Fatmawati, Jambi City. A sample of 30 postpartum mothers were given traditional massage. Data analysis of this study was conducted in univariate and bivariate using paired sample t-test. The results of univariate analysis before before body massage averaged 8.73 (not depressed) and after body massage an average of 6.80 was not mild depression. The results of bivariate analysis before and after body massage obtained P-Value = 0.000 (P <0.05), meaning that there was an influence on the level of mild depression in postpartum mothers. It is expected that PMB can conduct counseling on postpartum depression in order to increase maternal knowledge of the dangers of postpartum depression with body massage techniques to reduce the level of mild depression in postpartum mothers.